2014
DOI: 10.1016/j.jsha.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chylothorax on the early post operative outcome after pediatric cardiovascular surgery

Abstract: Chylothorax after pediatric cardiac surgery is not a rare complication. It occurs more commonly with single ventricle repair and aortic arch repair surgeries, and has a significant impact on the postoperative course and post operative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
1
29
1
1
Order By: Relevance
“…[10] In our study, three patients died (8.5%), which was similar to previous studies that had mortality rates of between 6 and 21%. [1,9,12,13] The cause of death in our patients was likely multifactorial due to the unfavorable hemodynamics, sepsis, and multiple organ dysfunction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[10] In our study, three patients died (8.5%), which was similar to previous studies that had mortality rates of between 6 and 21%. [1,9,12,13] The cause of death in our patients was likely multifactorial due to the unfavorable hemodynamics, sepsis, and multiple organ dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Allen et al [9] reported an incidence rate of 1% in their study in 1979 and 1987 while the latest reported incidence rates were 3.5% by Chan et al [3] and 5% by Ismail et al [10] The higher rates were likely due to the increased complexity of the patients along with the number of singleventricle repairs and redo surgeries. [3] The incidence of chylothorax in our study population was 3.1%, which Five of these patients had HLHS, and four underwent redo surgeries.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study population, the incidence of chylothorax was 1.1% over a 10-year period, which was slightly lower than the 1.18% of occurrence reported in the literature (for a population of 4,068 patients) (2,8,22). However, it is possible that the incidence is not related to the annual surgical volume.…”
Section: Discussioncontrasting
confidence: 66%
“…However, it is possible that the incidence is not related to the annual surgical volume. Usually, chylothorax appears between day 0-10 after injury to the thoracic duct, except in patients undergoing a vascular ring operation in which the surgical injury is certain (22). In the present study, the peak appearance of chylothorax was observed on the second postoperative day, which raises the possibility that chylothorax is a result of multiple precipitating factors presenting in the postoperative period.…”
Section: Discussionmentioning
confidence: 41%